2015
DOI: 10.1682/jrrd.2014.10.0260
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for job separations in a cohort of workers with psychiatric disabilities

Abstract: Abstract-We explored the relative effects of adverse working conditions, job satisfaction, wages, worker characteristics, and local labor markets in explaining voluntary job separations (quits) among employed workers with psychiatric disabilities. Data come from the Employment Intervention Demonstration Program in which 2,086 jobs were ended by 892 workers during a 24 mo observation period. Stepped multivariable logistic regression analysis examined the effect of variables on the likelihood of quitting. Over h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…Moreover, evidence suggests that managers and employers more generally have limited understanding or training regarding how to support workers with intellectual disabilities and those with mental health issues (Houtenville and Kalargyrou ). Managers are often not aware of appropriate disability management practices or effective recruitment and retention practices for people with disabilities (Cook and Burke‐Miller ; Lerner et al. ; MacDonald‐Wilson et al.…”
Section: Management and Employer Knowledge And Support For Workers Wimentioning
confidence: 99%
“…Moreover, evidence suggests that managers and employers more generally have limited understanding or training regarding how to support workers with intellectual disabilities and those with mental health issues (Houtenville and Kalargyrou ). Managers are often not aware of appropriate disability management practices or effective recruitment and retention practices for people with disabilities (Cook and Burke‐Miller ; Lerner et al. ; MacDonald‐Wilson et al.…”
Section: Management and Employer Knowledge And Support For Workers Wimentioning
confidence: 99%
“…Many managers need to be better acquainted with appropriate disability management practices and effective recruitment and retention practices for people with disabilities (Kulkarni & Valk, 2010). Despite some examples of excellent managerial practice and support of people with disabilities, a number of researchers argue that mainstream HRM does not sufficiently address the complexity surrounding disability or relationships between people with disabilities and organisations (Cook & Burke-Miller, 2015;Lerner et al, 2004;MacDonald-Wilson, Rogers, Massaro, Lyass, & Crean, 2002). Participation of workers with intellectual disabilities in the workplace will be affected by the type of HR practices that are employed by the organisation as well as the broader social climate.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, growing evidence suggests that workplace factors affect employment outcomes for people with disabilities (Kristman et al 2016). Research has shown that receipt of workplace accommodations is associated with better employment outcomes (Burkhauser et al 1995;Chow 2012;Cook et al 2015). Among VR applicants with psychiatric disabilities, accommodations such as flexible schedules and modified work duties were positively correlated with continued employment (Sevak and Khan 2017).…”
Section: Introductionmentioning
confidence: 99%